2022 Clinical practice guidelines for central precocious puberty of Korean children and adolescents - Su Jin Kim; Ji Hyun Kim; Yong Hee Hong; In Hyuk Chung; Eun Byoul Lee; Eungu Kang; Jinsup Kim; Aram Yang; Young-Jun Rhie; Eun-Gyong Yoo; Young-Lim Shin; Jin Ho Choi; et al. (Korean Society of Pediatric Endocrinology, 2023)
The Committee of Central Precocious Puberty of Korean Pediatrics and Adolescents of the Korean Society of Pediatric Endocrinology has newly developed evidence-based 2022 clinical practice guidelines for central precocious puberty in Korean children and adolescents. These guidelines provide the grade of recommendations, which includes both the strength of recommendations and the level of evidence. In the absence of sufficient evidence, recommendations are based on expert opinion. These guidelines have been revised and supplement the previous guidelines "Clinical Guidelines for Precocious Puberty 2011," and are drawn from a comprehensive review of the latest domestic and international research and the grade of recommendation appropriate to the domestic situation. This review summarizes the newly revised guidelines into 8 key questions and 27 recommendations and consists of 4 sections: screening, diagnosis, treatment, and long-term outcome of central precocious puberty.